Aggregation and Cooperative Effects in the Aldol Reactions of Lithium Enolates. Issue 41 (21st August 2013) - Larrañaga, Olatz; de Cózar, Abel; Bickelhaupt, F. Matthias; Zangi, Ronen; Cossío, Fernando P.
Abstract Density functional theory and Car–Parrinello molecular dynamics simulations have been carried out for model aldol reactions involving aggregates of lithium enolates derived from acetaldehyde and acetone. Formaldehyde and acetone have been used as electrophiles. It is found that the geometries of the enolate aggregates are in general determined by the most favorable arrangements of the point charges within the respective LinOn clusters. The reactivity of the enolates follows the sequence monomer≫dimer>tetramer. In lithium aggregates, the initially formed aldol adducts must rearrange to form more stable structures in which the enolate and alkoxide oxygen atoms are within the respective LinOn clusters. Positive cooperative effects, similar to allosteric effects found in several proteins, are found for the successive aldol reactions in aggregates. The corresponding transition structures show in general sofa geometries.